2013
DOI: 10.4067/s0717-73482013000100003
|View full text |Cite
|
Sign up to set email alerts
|

Asma infanto-juvenil y trastornos psiquiátricos

Abstract: Asthma and psychiatric disorders in childhood and adolescense Comorbid psychiatric disorders are common in asthma and can be divided into externalizing or internalizing disturbances. These conditions increase the morbidity of asthma in young people. Caregivers of asthmatic children are also susceptible to these diseases, which have been linked to the genesis and symptoms of asthma in children. Treatment of mental health disorders in children and caregivers should consider drugs, psychoeducation, family therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
(3 reference statements)
0
1
0
2
Order By: Relevance
“…More recently, it was found that administering long-term corticoid treatments reduces the serotonin levels in the blood and this could explain the onset of depressive symptoms (Vidal & Matamala, 2013). This matter is coherent with the psychological anguish observed in patients with severe asthma and prednisone dependants compared to those who did not show such dependence to prednisone (Amelink et al, 2014).…”
Section: Introductionmentioning
confidence: 78%
“…More recently, it was found that administering long-term corticoid treatments reduces the serotonin levels in the blood and this could explain the onset of depressive symptoms (Vidal & Matamala, 2013). This matter is coherent with the psychological anguish observed in patients with severe asthma and prednisone dependants compared to those who did not show such dependence to prednisone (Amelink et al, 2014).…”
Section: Introductionmentioning
confidence: 78%
“…Así, este resultado aporta evidencia de la necesidad de investigar aquellos factores que afectan de forma positiva al bienestar psicológico de los pacientes asmáticos. Sin embargo, es importante resaltar que la gran mayoría de los participantes presentan un buen control del asma, por lo que el grado de control de la enfermedad y la desregulación que su ausencia pudiera ocasionar en los asmáticos no estaría reflejado en nuestros resultados, tal y como indican Vidal y Matamala (2013).…”
Section: Discussionunclassified
“…Fijándonos en concreto en los pacientes que sufren asma bronquial, la evidencia apunta que los niños-adolescentes con asma tienen un mayor riesgo de presentar problemas emocionales y conductuales (McQuaid, Kopel, y Nassau, 2001). La presencia de consecuencias psicológicas se ha relacionado con la gravedad del asma, encontrándose una mayor prevalencia de dichos trastornos en asma severa y no contralada al compararla con asmáticos controlados o de menos severidad (Vidal y Matamala, 2013).…”
Section: Introductionunclassified